State-Religion Relations and Halal Governance: Islamic Legal Policy in Indonesia and Malaysia - Humaidi, M. Wildan; Ridwan; Salleh, Mohd Mahyeddin Mohd (Al-Manahij: Jurnal Kajian Hukum Islam, 2026)
The relationship between religion and the state has long been a subject of scholarly debate. This relationship is commonly classified into three dominant models: the integralist model, in which religion and the state are fully integrated; the secularist model, which maintains a strict separation between religious and political spheres; and the symbiotic-mutualistic model, which seeks a proportional balance between the two. This study examines how these frameworks are manifested in halal policy governance in Southeast Asia, with a particular focus on Indonesia and Malaysia. Employing a comparative qualitative approach, data were collected through document analysis, relevant scholarly sources, and interviews with key stakeholders. The findings indicate that constitutional recognition of religion does not necessarily determine the structure of halal policy governance. In Indonesia, halal policy is embedded within the state bureaucracy and religious authority through the Halal Product Assurance Law. In contrast, in Malaysia, halal certification is institutionalized under the Department of Islamic Development Malaysia (JAKIM), shaped by considerations of trade and economic development. In both cases, halal certification has evolved beyond a purely religious obligation into a strategic political–economic instrument with global relevance. This study concludes that halal governance reflects a hybridization of religious, political, and economic factors, highlighting the importance of analyzing halal policy within the framework of global political economy. The findings contribute theoretically to the growing field of halal political economy studies, particularly in understanding state–religion relations in Southeast Asia. Halal governance can no longer be viewed merely as an instrument of religious policy but has become a strategic domain within the global political economy.